MENANGANI PENOLAKAN KARYAWAN MELALUI ADKAR MODEL - Eisye Tandelilin (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2006)
More and more organizations today face a dynamic and changing environment. This, in turn, is requiring these organizations to adapt. “Change or die